Effect Of Foreign Direct Investment (FDI) On Nigeria’s Economic Growth - Adewale, Abass (Airlangga Journal of Innovation Management, 2025)
Foreign direct investment (FDI) serves as a crucial engine for the economic growth of emerging nations such as Nigeria. Despite its recognized importance, the extent of FDI’s contribution to Nigeria’s economic performance remains uncertain due to macroeconomic instability and structural weaknesses. The objective of this study is to examine the effect of FDI on Nigeria’s economic growth between 2001 and 2023, while considering the influence of exchange rate, inflation rate, and interest rate as key explanatory variables. The study employed an ex-post facto research design using annual secondary data sourced from the Central Bank of Nigeria Statistical Bulletin. Ordinary Least Squares (OLS) regression analysis was adopted to estimate the relationships among variables. The results revealed that FDI exerts a positive but statistically insignificant impact on real gross domestic product (RGDP), while interest rate shows a significant positive influence on economic growth. Exchange rate and inflation rate exhibit weak and insignificant effects. The findings conclude that monetary policy remains an essential driver of economic growth in Nigeria, whereas FDI alone contributes minimally without complementary reforms. It is recommended that policymakers create stable macroeconomic environments, enhance investment infrastructure, and ensure consistent policy frameworks to attract sustainable foreign investments. Future studies should explore sector-specific FDI dynamics and their differential impacts on economic performance. The research provides managerial implications for investors and policy implications for economic planners seeking long-term growth through effective FDI utilization.